ANALISIS PENGAMBILAN KEPUTUSAN PETANI TEBU TERHADAP KREDIT KETAHANAN PANGAN DAN ENERGI (Studi Kasus di Desa Bakalan Kecamatan Bululawang Kabupaten Malang) - Ninin Khoirunnisa; Farah Mutiara (OPTIMA, 2017)
Farming income from sugar cane can be improved by the application of technology sugar cane farming and supported by existing capital. This research aims to describe the implementation of Kredit Ketahanan Pangan dan Energi (KKP-E) and analyze factors that affect sugarcane farmers in making decision the KKP-E. Research was filmed in the Bakalan Village Bululawang Subdistrict Malang District. Sample determination was done by using simple random sampling method. The data was collected by using interview, observation and documentation methods. Analysis data method used were descriptive qualitative and quantitative analysis. The results of study showsthat implementation of the KKP-E which was done in the area of research was right on target, but the goal of the KKP-E programs has not been fully achieved. In the meantime of logit analysis, socio-economic factors which affecting the decision making farmers KKP-E that is land farmers and number of household dependents sugar cane farmers. Suggestions may be submitted: (1) the supervision and evaluation of the implementation of the KKP-E programs, and (2) to the next, expected to analyze the research or put other variables such as length of sugar cane farming and interest of KKP-E that expected can be affect decision making farmers credit.